2019
DOI: 10.1002/cptc.201900252
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Enhanced Photoluminescence and Photocatalysis Reactions in Metal‐Semiconductor Nanomaterials: UV‐Generated Hot Electron in Gold‐Zinc Oxide

Abstract: Herein, we introduce a mechanistic study to design a hybrid junction in metallic‐semiconductor (M/SC) nanostructures. UV‐light‐induced hot electron generation in ZnO nanostructures is used to precisely tune the photoluminescence (PL) and photocatalytic (PC) properties in hybrid Au/ZnO nanomaterials. Both enhancement and quenching of the PL and PC functionalities are observed, depending on the properties of the Au nanoparticles (AuNPs) and the Au/ZnO molecular distance. Under UV irradiation free‐ligand AuNPs qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Akil et al designed and optimized a nanostructure consisting of metal/semiconductor, i.e., Au–ZnO in order to enhance both photocatalytic and photoluminescence properties of the hybrid material under visible light irradiation (Figure c). It was shown that by using CTAB as a shell of AuNPs and spacer between two components, the photoluminescence characteristic of ZnO as a result of the SPR effect of AuNPs was enhanced.…”
Section: Plasmon-enhanced Photocatalysis For Environmental Remediationmentioning
confidence: 99%
See 2 more Smart Citations
“…Akil et al designed and optimized a nanostructure consisting of metal/semiconductor, i.e., Au–ZnO in order to enhance both photocatalytic and photoluminescence properties of the hybrid material under visible light irradiation (Figure c). It was shown that by using CTAB as a shell of AuNPs and spacer between two components, the photoluminescence characteristic of ZnO as a result of the SPR effect of AuNPs was enhanced.…”
Section: Plasmon-enhanced Photocatalysis For Environmental Remediationmentioning
confidence: 99%
“…To conclude, these perfect results came from improved photocatalytic activities originating from the plasmon-enhanced photoabsorption and rapid separation of photogenerated electron−hole pairs in the heterostructure as shown in Figure 3b. Akil et al 37 designed and optimized a nanostructure consisting of metal/semiconductor, i.e., Au−ZnO in order to enhance both photocatalytic and photoluminescence properties of the hybrid material under visible light irradiation (Figure 3c). It was shown that by using CTAB as a shell of AuNPs and spacer between two components, the photoluminescence characteristic of ZnO as a result of the SPR effect of AuNPs was enhanced.…”
Section: Plasmon-enhanced Photocatalysis For Environmental Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface decoration of semiconductor nanostructures with metallic nanoparticles (NPs) usually leads to an improvement of their catalytic and electrical properties [ 10 , 11 , 12 , 13 , 14 ]. The formation of nano-Schottky junctions at the metal–semiconductor interface leads to the creation of a strong electric field directed toward the surface and to a significant modification of the ZnO NRs energy band profiles [ 15 , 16 , 17 , 18 , 19 ]. As a consequence, space charge regions and surface-localized electric fields promote a catalytic effect and modify the radiative recombination process.…”
Section: Introductionmentioning
confidence: 99%
“…Such a process could be the consequence of a significant bending of electronic energy bands into ZnO just below the metal nanoparticle, inducing free carrier depletion. Such an effect in decorated ZnO nanorods allows the application of these composite materials in UV sensing and light-induced catalysis [ 11 , 16 , 18 , 19 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%